Architected UHMWPE simulating trabecular bone tissue. (March 2018) - Senatov, F.S.; Niaza, K.V.; Salimon, A.I.; Maksimkin, A.V.; Kaloshkin, S.D.
Graphical abstract: Highlights: A newly developed method for creating architectured trabecular bone tissue scaffolds out of strong of UHMWPE is presented. The method was successfully validated by manufacturing 3D-architectured UHMWPE scaffolds. The method allows the creation of geometrically anisotropic pore cells with 0.7–3 mm diameter and 1.4 mm wall thickness. Abstract: Architected UHMWPE 3D open-cell porous scaffolds simulating anisotropic trabecular bone tissue were designed and produced by a combination of 3D-printing, powder filling and hot molding, and final leaching. SEM investigations confirmed the high perfection of the struts and nodes in the open cell architecture with pore diameters in the range 0.7–3 mm. The scaffold surface texture was characterized by 250 μm asperities formed by templating of UHMWPE on the surface of PLA sacrificial 3D-printed matrix.